Altman Z-Score Model, Springate, Grover, Ohlson and Zmijweski to Assess the Financial Distress Potential of PT. Garuda Indonesia Tbk During and After the Covid-19 Pandemic - Agung Anggoro Seto (Institute of Computer Science (IOCS), 2022)
This study aimed to assess PT. Garuda Indonesia Tbk's potential for financial distress during and after the covid-19 pandemic. This research employed descriptive quantitative type; it described the potential for financial distress at PT. Garuda Indonesia Tbk. Secondary data were utilised, namely the financial statements of PT. Garuda Indonesia Tbk for the years 2018-2021. Data collection approaches involving documentation and literature study. The data analysis method utilised descriptive analysis with the research variable of financial distress. This study's five models used to measurement financial distress were Z-Score Altman, Springate, Grover, Ohlson, and Zmijweski. The findings indicate that PT. Garuda Indonesia Tbk is in a condition of financial distress or has the potential to declare bankruptcy between 2018 and 2021, which determined using the Z-Score Altman, Springate, Grover, Ohlson, and Zmijweski methods.